Caspase 3–mediated stimulation of tumor cell repopulation during cancer radiotherapy - Huang, Qian; Li, Fang; Liu, Xinjian; Li, Wenrong; Shi, Wei; Liu, Fei-Fei; O'Sullivan, Brian; He, Zhimin; Peng, Yuanlin; Tan, Aik-Choon; Zhou, Ling; Shen, Jingping; et al. (Nature medicine, 2011)
Cytotoxic cancer therapy can induce accelerated growth of surviving cancer cells, a phenomenon known as tumor repopulation. This report uncovers a mechanism by which caspase 3 activation in treated cells promotes growth of surviving cells, mediated by iPLA 2 and PGE 2 . The level of caspase 3 activation in human tumors also correlates with risk of relapse, suggesting that this pathway may be a determinant of therapeutic effects. In cancer treatment, apoptosis is a well-recognized cell death mechanism through which cytotoxic agents kill tumor cells. Here we report that dying tumor cells use the apoptotic process to generate potent growth-stimulating signals to stimulate the repopulation of tumors undergoing radiotherapy. Furthermore, activated caspase 3, a key executioner in apoptosis, is involved in the growth stimulation. One downstream effector that caspase 3 regulates is prostaglandin E 2 (PGE 2 ), which can potently stimulate growth of surviving tumor cells. Deficiency of caspase 3 either in tumor cells or in tumor stroma caused substantial tumor sensitivity to radiotherapy in xenograft or mouse tumors. In human subjects with cancer, higher amounts of activated caspase 3 in tumor tissues are correlated with markedly increased rate of recurrence and death. We propose the existence of a cell death–induced tumor repopulation pathway in which caspase 3 has a major role.